Sanded fabric easy to clean and preparation method thereof

By blending the first fiber and the second fiber and using a hexacarbon alkyl fluoride finishing agent, an easy-to-clean fray fabric is prepared, which solves the problem of degradation of mechanical properties of the fray fabric easily adsorbs dirt during use and post-organization process, and achieves efficient cleaning of the fabric and maintaining mechanical properties.

CN119640584APending Publication Date: 2025-03-18LUOLAI LIFESTYLE TECH CO LTD +1

Patent Information

Application Number
CN202411704836.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During use, grinding fabrics are prone to absorb tiny particles such as dust and dandruff, and their mechanical properties are degraded during the post-organization process, making them prone to hair loss, making it difficult to clean.

Method used

By blending the first fiber and the second fiber into a grey fabric, using hexacarbon alkyl fluoride as finishing agent, combined with post-organization technology, a short-fluffy hydrophilic and long-fluffy hydrophobic oleophobic fabric was prepared.

Benefits of technology

It is achieved that the fabric is not easily wetted by water-based and oily dirt when used, and it is easy to wash off once the fabric is stained, solving the problem of difficult cleaning of the worn fabric and degraded mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a sanded fabric easy to clean and a preparation method thereof. The preparation method of the easy-to-clean sanded fabric comprises the steps that first fibers and second fibers are blended into gray fabric, the gray fabric is subjected to the procedures of turning sewing, singeing, fading, scouring and bleaching, pre-shaping, sanding, cleaning, shaping, after-finishing and drying in sequence, a finishing agent adopted in finishing liquid in the after-finishing process comprises hexa-carbon alkyl fluoride, the moisture regain of the first fibers is larger than or equal to 8%, and the moisture regain of the second fibers is larger than or equal to 8%; the difference value of the dry heat shrinkage rate between the first fiber and the second fiber at the temperature of 130 DEG C is greater than or equal to 5%. Compared with the prior art, the sanding fabric has the advantages that the principle that two layers of different hydrophilic and hydrophobic surfaces are formed by the heat shrinkage difference between the first fiber and the second fiber is fully utilized, the sanding fabric with hydrophilic short fluff and hydrophobic and oleophobic long fluff is prepared in combination with an after-finishing technology, and hexa-carbon alkyl fluoride capable of being subjected to low-temperature after-finishing is selected as a finishing agent, so that the fabric is more comfortable to wear. The technical problem that in the after-finishing process, the mechanical performance of the sanded fabric is reduced, and hair is prone to falling is solved. The sanded fabric provided by the invention cannot be wetted by water-based and oily dirt to form stains when in use, and the fabric is easy to wash away once being stained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of textiles, and in particular to an easy-to-clean sanded fabric and a preparation method thereof. Background Art

[0002] Brushing, also known as sanding or velvet finishing, refers to the process of using sanding rollers (or belts) to create a fuzzy surface on a fabric. Brushed fabrics are the result of this treatment. While retaining the fabric's original properties, this process creates a short, fuzzy surface. This creates a new look, reduces thermal conductivity, and increases warmth and softness. Brushed fabrics offer striking colors, a soft hand, and a full, pleasing appearance. Brushed fabrics offer a fluffy, full-bodied appearance, a soft feel, a rich texture, comfort, a strong drape, excellent warmth retention, and are easy to care for. They have a rich, velvety surface and are resistant to fading and pilling. They are widely used in textiles such as bed sheets, quilt covers, and pillowcases. However, the special surface treatment of brushed fabrics creates a fuzzy surface, making them relatively rough. This rough surface easily attracts particles such as dust and dander. Skin oils and sweat can also adhere to the fabric during use, making it difficult to clean.

[0003] The ideal easy-to-clean fabric is one that exhibits strong hydrophobicity and oleophobicity in its dry state, yet exhibits a certain degree of hydrophilicity and good stain release properties when exposed to water. In other words, the fabric must possess both hydrophilic and hydrophobic properties. Currently, this approach primarily involves using hydrophobic and oleophobic agents in conjunction with conventional hydrophilic polyethylene glycol ethers to achieve a synergistic effect. However, fabrics treated with both hydrophilic and hydrophilic finishing processes are less hydrophilic and less hydrophobic than fabrics treated with only hydrophilic and oleophobic modifications. A polyurethane-modified fluoropolyacrylate stain release finish (FPUA) has been described. This finish contains both fluorinated hydrophobic and hydrophilic groups. In air, the fluoroalkyl groups form a crystalline structure, creating a hydrophobic surface. In water, the hydrophilic compounds transfer to the surface, creating a hydrophilic surface. However, using this finish requires a relatively high operating temperature, which can further reduce the mechanical strength of sanded fabrics. This also results in significant cleaning losses and linting, making it unsuitable for sanded fabric finishing. Furthermore, fluorinated stain release finishes are rarely reported. Summary of the Invention

[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides an easy-to-clean sanded fabric and a preparation method thereof to solve the technical problems that the sanded fabric is easy to hide dirt and grime, difficult to clean, and has large mechanical losses and is easy to shed after finishing.

[0005] To achieve the above objectives, the solution of this application is as follows: In a first aspect, the present invention provides a method for preparing an easy-to-clean sanded fabric, the method comprising the following steps: The first fiber and the second fiber are blended into a grey cloth, and the cloth is sequentially subjected to the steps of seaming, singeing, bleaching, pre-setting, sanding, cleaning, shaping, finishing and drying to obtain the easy-to-clean sanded fabric. The finishing agent in the finishing liquid used in the finishing process includes a hexaalkyl fluoride, the mass water absorption rate of the first fiber is ≥8%, and the difference in dry heat shrinkage between the first fiber and the second fiber at a temperature of 130°C is ≥5%.

[0006] Optionally, the first fiber is selected from at least one of cotton fiber, viscose fiber and modal fiber.

[0007] Optionally, the second fiber is selected from polyester fibers.

[0008] Optionally, the mass ratio of the first fiber to the second fiber is 35-65:65-35.

[0009] Optionally, during the sanding process, the rotation speed of the sanding equipment used is 800-1200 r / min, preferably 900-1200 r / min; the vehicle speed is 15-20 m / min, preferably 16-20 m / min; and the tension is 0.3-0.5 MPa, preferably 0.35-0.5 MPa.

[0010] Optionally, the pre-forming temperature is 85-120° C., preferably 90-120° C.; the pre-forming time is 4-6 seconds, preferably 5-6 seconds.

[0011] Optionally, the shaping temperature is 80-120° C., preferably 85-120° C.; the shaping time is 1-3 min, preferably 1.5-3 min.

[0012] Optionally, in the finishing liquid, the concentration of the hexaalkyl fluoride is 4 wt %-6 wt %, preferably 4.5 wt %-6 wt %.

[0013] Optionally, during the post-finishing process, the pressure of the rolling groove used is 2-4 kg / cm 2 , preferably 2.5-4kg / cm 2 .

[0014] Optionally, the mass ratio of the grey cloth to the finishing liquid is 1:10-15, preferably 1:12-15.

[0015] Optionally, during the post-finishing process, the liquid squeeze rate is 70%-75%, preferably 72%-75%.

[0016] Optionally, the drying temperature is 120-135° C., and the drying time is 3-5 minutes, preferably 3.5-5 minutes.

[0017] In a second aspect, the present invention also provides an easy-to-clean sanded fabric prepared according to the method described above.

[0018] Beneficial effects of the present invention: This application makes full use of the principle of forming two layers of surfaces with different hydrophilic and hydrophobic properties between the first fiber and the second fiber, and combines post-finishing technology to prepare a sanded fabric with short-hair hydrophilicity and long-hair hydrophobic and oleophobicity, and selects hexaalkyl fluoride that can be post-finished at low temperature as a finishing agent, which solves the technical problem of sanded fabrics suffering from decreased mechanical properties and easy shedding during the post-finishing process.

[0019] The present invention provides a sanded fabric that will not be wetted by water-based and oily dirt to form stains during use and can be easily washed off once the fabric is stained. The invention solves the technical problem of the lack of mature easy-to-clean finishing agents and provides a method for preparing easy-to-clean sanded fabrics with low process difficulty, which can realize industrial production. DETAILED DESCRIPTION

[0020] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0021] One embodiment of the present invention provides a method for preparing an easy-to-clean sanded fabric, comprising the following steps: The first fiber and the second fiber are blended into a grey fabric, and the fabric is sequentially subjected to the steps of seaming, singeing, bleaching, pre-setting, sanding, cleaning, setting, finishing and drying to obtain an easy-to-clean sanded fabric. The finishing agent used in the finishing process includes a hexaalkyl fluoride in the finishing liquid, and the concentration of the hexaalkyl fluoride in the finishing liquid is 4wt%-6wt%. The mass water absorption rate of the first fiber is ≥8%, the dry heat shrinkage rate of the first fiber is greater than the dry heat shrinkage rate of the second fiber, and the difference in dry heat shrinkage rate between the first fiber and the second fiber is ≥5%; The first fiber is selected from at least one of cotton fiber, viscose fiber and modal fiber; The second fiber is selected from polyester fibers; During the sanding process, the speed of the sanding equipment used is 800-1200r / min, the speed is 15-20m / min, and the tension is 0.3-0.5MPa; The pre-forming temperature is 85-120℃ and the pre-forming time is 4-6s; The setting temperature is 80-120℃ and the setting time is 1-3 minutes; During the finishing process, the pressure of the rolling groove used is 2-4kg / cm 2 , the mass ratio of grey cloth to finishing liquid is 1:10-15, and the squeezing rate is 70%-75%; The drying temperature is 125-135°C and the drying time is 3-5 minutes.

[0022] Another embodiment of the present invention further provides an easy-to-clean sanded fabric produced according to the method described above.

[0023] In the following description, numerous details are set forth to provide a more thorough explanation of the embodiments of the present invention; however, it is apparent to one skilled in the art that the embodiments of the present invention may be practiced without these specific details.

[0024] Example 1 The preparation method of easy-to-clean sanded fabric includes the following steps: S1. Cotton fiber (long-staple cotton, with a mass water absorption of 8.4% and a dry heat shrinkage of 5.9% at 130°C) and polyester fiber (with a dry heat shrinkage of 0.8% at 130°C) were blended in a mass ratio of 65:35 to produce a greige fabric with a width of 267 cm, 50D*50D*60S, and an area density of 133*72 strands per square inch. Clearly, the dry heat shrinkage of the cotton fiber was higher than that of the polyester fiber, with a difference of 5.1%. S2. The fabric obtained in step S1 was sequentially seamed, singed, and bleached, then pre-formed at 100°C for 5 seconds and then sanded using an Italian SM-1 sanding machine. During the sanding process, the sanding roller speed was 1000 rpm, the spacing was 3 mm, the speed was 18 m / min, the wrap angle was 5°, and the tension was 0.4 MPa. S3. The sanded fabric was cleaned three times using a jigger and then set at 110°C for 2 minutes. S4. The commercially available Deco Nano Texnology® FCB058 three-proof finishing agent (active ingredient is hexacarbon alkyl fluoride) and water were mixed and stirred to obtain a concentration of 5wt% of the finishing liquid FCB058 three-proof finishing agent; The shaped grey fabric is immersed in a finishing liquid 12 times its mass, and then rolled. The pressure of the rolling groove is 3kg / cm 2 , the liquid squeeze rate is 72%; S5. Drying the post-finished grey fabric at 130° C. for 4.5 min to obtain an easy-to-clean brushed fabric.

[0025] Example 2 The preparation method of easy-to-clean sanded fabric includes the following steps: S1. Viscose fiber (mass water absorption rate of 12.7% and dry heat shrinkage of 6.3% at 130°C) and polyester fiber (dry heat shrinkage of 0.8% at 130°C) were blended in a 50:50 mass ratio to produce a greige fabric with a width of 267 cm, 50D*50D*60S, and an area density of 133*72 strands per square inch. Clearly, the dry heat shrinkage of the viscose fiber was higher than that of the polyester fiber, with a difference of 5.5%. S2. The fabric obtained in step S1 was sequentially seamed, singed, and bleached, then pre-formed at 85°C for 6 seconds and then sanded using an Italian SM-1 sanding machine. During the sanding process, the sanding roller speed was 800 rpm, the spacing was 3 mm, the speed was 15 m / min, the wrap angle was 5°, and the tension was 0.5 MPa. S3. The sanded fabric was cleaned three times using a jigger and then set at 80°C for 1 minute. S4. The commercially available Deco Nano Texnology® FCB058 three-proof finishing agent (active ingredient is hexacarbon alkyl fluoride), stirred evenly to obtain a concentration of 5wt% of the finishing liquid FCB058 three-proof finishing agent; The shaped grey fabric is immersed in a finishing liquid 15 times its mass, and then rolled. The pressure of the rolling groove is 4kg / cm 2 , the liquid squeeze rate is 75%; S5. Drying the post-finished grey fabric at 125° C. for 5 minutes to obtain an easy-to-clean brushed fabric.

[0026] Example 3 The preparation method of easy-to-clean sanded fabric includes the following steps: S1. Modal fiber (mass water absorption rate of 13.3% and dry heat shrinkage of 6.0% at 130°C) and polyester fiber (dry heat shrinkage of 0.8% at 130°C) were blended in a mass ratio of 35:65 to produce a greige fabric with a width of 267 cm, 50D x 50D x 60S, and an area density of 133 x 72 strands per square inch. The dry heat shrinkage of modal fiber was significantly higher than that of polyester fiber, with a difference of 5.2%. S2. The fabric obtained in step S1 was sequentially seamed, singed, and bleached, then pre-formed at 120°C for 4 seconds and then sanded using an Italian SM-1 sanding machine. During the sanding process, the sanding roller speed was 1200 rpm, the spacing was 3 mm, the speed was 20 m / min, the wrap angle was 5°, and the tension was 0.3 MPa. S3. The sanded fabric was cleaned three times using a jigger and then set at 120°C for 3 minutes; S4. The commercially available Deco Nano Texnology® FCB058 three-proof finishing agent (active ingredient is hexacarbon alkyl fluoride) and water were mixed and stirred to obtain a concentration of 5wt% of the finishing liquid FCB058 three-proof finishing agent; The shaped grey fabric is immersed in a finishing liquid 10 times its mass, and then rolled. The pressure of the rolling groove is 2kg / cm 2 , the liquid squeeze rate is 70%; S5. Drying the post-finished grey fabric at 135° C. for 3 minutes to obtain an easy-to-clean brushed fabric.

[0027] Performance testing According to GB / T3923.1-2013 Tensile Properties of Textile Fabrics, the breaking strength of the grey fabric after shaping, before finishing, and after drying in Example 1 was tested. The results are shown in Table 1.

[0028] Table 1 Breaking strength test results

[0029] As shown in Table 1, there was no significant change in breaking strength in Example 1 before and after finishing. This result demonstrates that, unlike solvent-based polyurethane-modified fluoropolyacrylate stain-release finishers (FPUA), which require relatively high temperatures, this application utilizes a hexaalkyl fluoride, which has a lower temperature requirement, as a finishing agent, resolving the prior art issue of decreased mechanical properties of fabrics after finishing. Specifically, this application leverages the principle of forming two surfaces with different hydrophilic and hydrophobic properties by utilizing the difference in thermal shrinkage between the first and second fibers. Combined with post-finishing technology, this application produces a sanded fabric with short-hair hydrophilicity and long-hair hydrophobicity. Furthermore, the application uses a hexaalkyl fluoride, which can be post-finished at low temperatures, as a finishing agent, resolving the prior art issue of decreased mechanical properties and linting of sanded fabrics during post-finishing.

[0030] The hydrophobicity of the fabric prepared in Example 1 was tested using the AATCC Technical Manual / 2004 Water Repellency, Spray Test (i.e., water repellency test). The test results are shown in Table 2, where a score of 0 indicates that the upper and lower surfaces of the fabric are completely wetted, a score of 50 indicates that the upper and lower surfaces of the fabric are completely wetted, and a score of 100 indicates that neither the upper nor lower surfaces of the fabric are wetted. The results are shown in Table 2. After 100 washes (washing parameters: high water level, 100g of Tide laundry detergent, a total wash load of 4lb, 12 minutes, and 100 washes), the hydrophobicity of the fabric prepared in Example 1 was tested again. The results are shown in Table 2. The oleophobic properties of the brushed fabric prepared in Example 1 were tested, specifically, according to the AATCC Technical Manual / 2004 Oil Repellency, Spray Test method (i.e., oil repellency test). The test oil was dropped onto the fabric with a dropper and the oil penetration was observed after 30 seconds. If no oil penetrated, the fabric passed the test level. The test was conducted first with oils having low surface tension, then with oils having high surface tension, until the test failed. The test level ranged from 0 to 8, with the higher the level, the better the oleophobic properties. The test results are shown in Table 2. After 100 washes (washing parameters: high water level, 100g of Tide laundry detergent, a total load of 4lb of wash cloth, 12 minutes of washing, and 100 washes), the oleophobic properties of the fabric prepared in Example 1 were tested again. The results are shown in Table 2. The stain removal performance of the sanded fabric prepared in Example 1 was tested, specifically as follows: referring to the AATCC Technical Manual / 130-2000 Soil Release, Spray Test method (i.e., oil removal performance test), the fabric sample was conditioned at 21°C and a relative humidity of 65% for 4 hours, and then placed flat on a single layer of AATCC absorbent paper. Five drops (about 0.2 mL) of corn oil were dropped onto the sample surface using a dropper, and the oily area was covered with cellophane. An external force was applied for 60 seconds, and the fabric sample was taken out for washing. During the washing, a high water level was used, 100 g of Tide laundry detergent was added, and a wash cloth with a total load of 4 lb was added. The washing was performed for 12 minutes, and the sample card was used for comparison. The experimental grade was 0-5, and the higher the grade, the less oily residue, that is, the better the stain removal performance, and the lower the grade, the more oily residue, that is, the worse the stain removal performance. The results are shown in Table 2. The fabric sample was washed 100 times (washing parameters were: high water level, 100 g of Tide laundry detergent, and 4 lb of Tide laundry detergent were added). Tide laundry detergent was added to a wash cloth with a total load of 4 lb, and the washing process was repeated for 12 minutes. This was repeated 100 times. The stain removal performance of the fabric prepared in Example 1 was tested again. The results are shown in Table 2.

[0031] Table 2 Hydrophobicity, oleophobicity and stain removal test results

[0032] As shown in Table 2, there was no significant change in the hydrophobicity, oleophobicity, and stain removal properties of the sanded fabric of Example 1 before and after washing. This result shows that the present application uses a second polyester fiber having no active functional groups such as hydroxyl groups on the surface and low thermal shrinkage, and a first fiber having a large number of hydroxyl groups on the surface, strong hygroscopic properties, and high thermal shrinkage as raw materials to make a greige fabric. After sanding, finishing, and shaping, the fabric surface is formed. The second fiber having no active functional groups such as hydroxyl groups on the surface and low thermal shrinkage forms long hairs floating on the fabric surface, giving the fabric hydrophobic and oleophobic self-cleaning properties. The hydrophobic and oleophobic self-cleaning properties of the fabric are further enhanced by the hexaalkyl fluoride. The first fiber having a large number of hydroxyl groups on the surface, strong hygroscopic properties, and high thermal shrinkage forms short hairs located inside the long hairs, making the fabric easy to hydrate after being stained, thereby facilitating the removal of stains during subsequent washing. In addition, the use of hexaalkyl fluoride as a finishing agent can impart long-lasting hydrophobic and oleophobic properties and stain removal properties to the fabric.

[0033] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, any equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A method for preparing an easy-to-clean sanded fabric, characterized in that: The preparation method comprises the following steps: The first fiber and the second fiber are blended into a grey cloth, and the fabric is sequentially subjected to the steps of seaming, singeing, bleaching, pre-forming, sanding, cleaning, shaping, finishing and drying to obtain the easy-to-clean sanded fabric. The finishing agent in the finishing liquid used in the finishing process includes a hexaalkyl fluoride, the mass water absorption rate of the first fiber is ≥8%, and the difference in dry heat shrinkage rate between the first fiber and the second fiber at a temperature of 130°C is ≥5%.

2. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: The first fiber is selected from at least one of cotton fiber, viscose fiber and modal fiber.

3. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: The second fibers are selected from polyester fibers.

4. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: During the sanding process, the rotation speed of the sanding equipment used is 800-1200 r / min, the vehicle speed is 15-20 m / min, and the tension is 0.3-0.5 MPa.

5. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: The pre-forming temperature is 85-120°C, and the pre-forming time is 4-6s; And / or, the shaping temperature is 80-120° C., and the shaping time is 1-3 min.

6. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: In the finishing liquid, the concentration of the hexaalkyl fluoride is 4wt%-6wt%.

7. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: During the post-finishing process, the pressure of the rolling groove used is 2-4kg / cm 2 .

8. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: The mass ratio of the grey cloth to the finishing liquid is 1:10-15; And / or, during the post-finishing process, the liquid extraction rate is 70%-75%.

9. The method for preparing the easy-to-clean sanded fabric according to claim 1, characterized in that: The drying temperature is 125-135° C., and the drying time is 3-5 min.

10. An easy-to-clean sanded fabric obtained according to the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Sanding fabric with stereoscopic layer effect and preparation method of sanding fabric

    CN110644173A

  • Easy-to-wipe decontamination fabric and preparation method thereof

    CN113279246A

  • Processing method of non-ironing and waterproof sanded fabric

    CN113981685A

  • Novel sanded waterproof and oil-proof fabric and production process thereof

    CN117721636A

Cited By

  • Long-acting super-hydrophobic fabric and preparation method thereof

    CN118007407A